Greater widespread functional connectivity of the caudate in older adults who practice kripalu yoga and vipassana meditation than in controls - Gard, Tim; Taquet, Maxime; Dixit, Rohan; Hölzel, Britta K.; Dickerson, Bradford C.; Lazar, Sara W. (Frontiers in Human Neuroscience, 2015)
There has been a growing interest in understanding how contemplative practices affect brain functional organization. However, most studies have restricted their exploration to predefined networks. Furthermore, scientific comparisons of different contemplative traditions are largely lacking. Here we explored differences in whole brain resting state functional connectivity between experienced yoga practitioners, experienced meditators and matched controls. Analyses were repeated in an independent sample of experienced meditators and matched controls. Analyses utilizing Network Based Statistics (NBS; Zalesky et al., 2010) revealed difference components for yoga practitioners > controls and meditators > controls in which the right caudate was a central node. Follow up analyses revealed that yoga practitioners and meditators had significantly greater degree centrality in the caudate than controls. This greater degree centrality was not driven by single connections but by greater connectivity between the caudate and numerous brain regions. Findings of greater caudate connectivity in meditators than in controls was replicated in an independent dataset. These findings suggest that yoga and meditation practitioners have stronger functional connectivity within basal ganglia cortico-thalamic feedback loops than non-practitioners. Although we could not provide evidence for its mechanistic role, this greater connectivity might be related to the often reported effects of meditation and yoga on behavioral flexibility, mental health and well-being.